Long-lasting Corolla Cultivars in Japanese Azaleas: A Mutant AP3/DEF Homolog Identified in Traditional Azalea Cultivars from More Than 300 Years Ago - Cheon, Kyeong-Seong; Nakatsuka, Akira; Tasaki, Keisuke; Kobayashi, Nobuo (Frontiers in Plant Science, 2018)
Floral shape in higher plants typically requires genetic regulation through MADS transcription factors. In Japan, hundreds of azalea cultivars including flower shape mutations have been selected from the diversity of endogenous species and natural hybrids since the early 17th century, the Edo era (1603 to 1867). The long-lasting trait, known as “Misome-shō” in Japanese, has been identified in several species and cultivar groups of evergreen azaleas (Rhododendron L.) from three hundred years ago in Japan. However, the natural mutation conferring the long-lasting trait in azalea remains unknown. Here, we showed MADS-box gene mutations in long-lasting flowers, R. kaempferi ‘Nikkō-misome’, R. macrosepalum ‘Kochō-zoroi’, R. indicum ‘Chōjyu-hō’, and R. × hannoense ‘Amagi-beni-chōjyu’. All of the long-lasting flowers exhibited small-sized corollas with stomata during long blooming. In the long-lasting flowers, transcript of the APETALA3 (AP3)/DEFICIENS (DEF) homologue was reduced, and an LTR-retrotransposon was independently inserted into exons 1, 2, and 7 or an unknown sequence in exon 1 in gDNA of each cultivar. This insertion apparently abolished the normal mRNA sequence of the AP3/DEF homologue in long-lasting flowers. Also, long-lasting flowers were shown from F2 hybrids that had homozygous ap3/def alleles. Therefore, we concluded that the loss of function of the AP3/DEF homologue through a transposable element insertion may confer a stable long-lasting mutation in evergreen azaleas.